The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1192/bjo.2022.25
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 pandemic on mental health in individuals with pre-existing mental illness

Abstract: Background There is evidence that the COVID-19 pandemic has negatively affected mental health, but most studies have been conducted in the general population. Aims To identify factors associated with mental health during the COVID-19 pandemic in individuals with pre-existing mental illness. Method Participants (N = 2869, 78% women, ages 18–94 years) from a UK cohort (the National Centre for Mental Health) with a history of mental illness completed a cross-sectional onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 45 publications
0
39
1
Order By: Relevance
“…Of the 10,017 participants invited to take part in the baseline survey, 3137 (31%) took part (Lewis et al, 2022). The majority of participants…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 10,017 participants invited to take part in the baseline survey, 3137 (31%) took part (Lewis et al, 2022). The majority of participants…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10,017 participants invited to take part in the baseline survey, 3137 (31%) took part (Lewis et al, 2022 ). The majority of participants (70.1%) completed the survey in the week commencing June 15th, 2020, with the remainder of the sample completing the survey between June 26th, 2020 and July 30th, 2020.…”
Section: Resultsmentioning
confidence: 99%
“…People with mental illness are more susceptible to infections during epidemics. This is probably due to higher rates of medical co-morbidities, but it may also be related to confined living arrangements, lower levels of personal protection behaviors, and lower awareness of risk [ 28 ]. It can also be related to the increased difficulties in accessing timely medical services.…”
Section: Increasing Disparities In Health Service Accessmentioning
confidence: 99%
“…The impact of the COVID-19 pandemic on mental health is now a widespread concern (Holmes et al, 2020), with a number of studies indicating substantial increases in mental ill-health (Robinson et al, 2022), particularly elevated anxiety, loneliness and psychological distress, and decreased life satisfaction and mental wellbeing throughout the pandemic (Kwong et al, 2020;Niedzwiedz et al, 2021;Patel et al, 2021;Santomauro et al, 2021). Despite the greater risk of severe physical illness from COVID-19 existing for older people (Pijls et al, 2021), population studies have highlighted the disproportionate effect of the pandemic on the mental health of younger people (Lewis et al, 2022;McGinty et al, 2020a;McGinty et al, 2020b;Niedzwiedz et al, 2021;Santomauro et al, 2021), likely influenced by job insecurity, financial pressures and education disruptions (Douglas et al, 2020;Gustafsson, 2020). Some groups have been identified as especially vulnerable to poor mental health during the pandemic; for example, those from the poorest households (Pierre et al, 2021) and those with a history of previous mental health problems (Kwong et al, 2020;Pierce et al, 2021;Warne et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of children and adolescents during the pandemic show that those with NDDs or special educational needs had the highest levels of mental health difficulties (Creswell et al, 2021), with reports of the majority of children with ASD experiencing either a worsening of their pre-pandemic psychiatric diagnoses and/or the development of new psychiatric symptoms (Vasa et al, 2021). Whilst longitudinal studies in children and adolescents have indicated worse mental health outcomes in those with NDDs, the limited studies in adults with ADHD and ASD have lacked pre-pandemic baseline assessments (Lewis et al, 2022), did not use longitudinal study designs or did not have repeated measurements during the pandemic (Kwong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%